The Influence of Financial Knowledge and Locus of Control on Personal Financial Management with Demographics as a Moderating Variable (Case Study on Generation Z) - Prakosa, Atang; Sari, Prima Yusi (Journal of Accounting Auditing and Business, 2024)
Nowadays, Generation Z is closely related to financial issues, which are connected to the increasing prevalence of financial technology in Indonesia. These issues include pay-later cases, problems regarding the understanding of online gambling, and a consumptive nature. This study aims to determine the influence of financial knowledge and locus of control on personal financial management, with demographics as a moderating variable. The study employs an experimental method using a 2 x 2 between-subjects design. The population of this study is Generation Z in Indonesia, divided into two groups: those who are employed and those who are not. The sample consists of 51 participants selected through purposive sampling. They were given manipulated cases adjusted to their profiles, and then asked to make financial decisions. The results of this study show a significant simultaneous influence of financial knowledge and locus of control on personal financial management, both with and without the moderating variable. However, individually, financial knowledge and locus of control cannot be moderated by demographics in their effect on personal financial management. Nonetheless, without the moderating variable, both financial knowledge and locus of control have a direct and partial influence on personal financial management